Analisis Etika Profesi Akuntansi Terhadap Perilaku Potensial Korupsi: Studi Kasus PT Pertamina - Tedy Dwi Saputra, Dwi Maharani Syahputri, M. Arista Sanjaya, Nurul Hidayah, Adellya Dewi Mustika (PT Wahana Global Education, 2025)
This study analyzes the influence of accounting professional ethics on corrupt practices within PT Pertamina, specifically focusing on the Riva Siahaan case. Employing a qualitative descriptive-analytic approach with secondary data, this research identifies five key factors contributing to corruption: (1) a permissive organizational culture, (2) intense performance pressure, (3) weaknesses in the internal control system, (4) violations of the accounting professional code of ethics, and (5) deficiencies in ethics education. Findings indicate that corruption at PT Pertamina stems from a complex systemic condition, not merely individual deviations. This research highlights the need for a holistic approach to corruption prevention, encompassing organizational culture transformation, strengthening of the control system, internalization of the code of ethics, and the development of comprehensive ethics education.